2009
DOI: 10.1074/jbc.m109.020701
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Schistosoma mansoni Thioredoxin-glutathione Reductase by Auranofin

Abstract: Schistosomiasis is a parasitic disease affecting over 200 million people currently treated with one drug, praziquantel. A possible drug target is the seleno-protein thioredoxin-glutathione reductase (TGR), a key enzyme in the pathway of the parasite for detoxification of reactive oxygen species. The enzyme is a unique fusion of a glutaredoxin domain with a thioredoxin reductase domain, which contains a selenocysteine (Sec) as the penultimate amino acid. Auranofin (AF), a gold-containing compound already in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
222
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 202 publications
(238 citation statements)
references
References 40 publications
(53 reference statements)
13
222
1
2
Order By: Relevance
“…Until now, we crystallized three different variants of SmTGR in four different space groups (this paper and Refs. 13,17). 5 The data show different crystallographic contacts but always the same overall architecture, suggesting the structure in solution and in the crystal is the same.…”
Section: Electrons Exit From the Tr Domain From The C Terminus To Eimentioning
confidence: 91%
See 1 more Smart Citation
“…Until now, we crystallized three different variants of SmTGR in four different space groups (this paper and Refs. 13,17). 5 The data show different crystallographic contacts but always the same overall architecture, suggesting the structure in solution and in the crystal is the same.…”
Section: Electrons Exit From the Tr Domain From The C Terminus To Eimentioning
confidence: 91%
“…The schistosomal antioxidant system lacks the typical mammalian TR and GR enzymes, which are both replaced by SmTGR; this peculiarity revealed that SmTGR may be a target of choice for the development of new antischistosomal drugs (5,13). Moreover, TGR enzymes with similar roles have been isolated in other human parasites, such as Taenia (14) and Echinococcus (15).…”
mentioning
confidence: 99%
“…We therefore performed some analysis of the full-length LcB structure, 437 residues of which could be accounted for in the electron density (Protein Data Bank code 2ETF). 5 The core structures of LcA and LcB are superimposable as are all serotypes with very little C␣ root mean square deviation. The presence of the loop between residues 415 and 425 makes the long helix (residues 425-437) very floppy so it can assume any orientation in LcB.…”
Section: Insight From Lcb Structurementioning
confidence: 99%
“…The LcB structure is from the Protein Data Bank (code 2ETF). 5 Green, C-terminal helix (residues 425-437); red, C-terminal loop; yellow, 60, 200, and 370 loops as indicated; blue, zinc atom bound at the active site.…”
Section: Insight From Lcb Structurementioning
confidence: 99%
See 1 more Smart Citation